THE TREATMENT OF EDUCATION AND HEALTH: OPPORTUNITIES REVEALED WITHIN THE SCHOOL AMBIT (Fiep Bulletin - online, 2012)
This study aimed to describe an experience of health at the school from a theoretical and practical experience in the school environment revealed in a pilot project "Servant Health" involving servants of a Campus of the Federal Institute of Education, Science and Technology of Pernambuco (IFPE), analyzing the lifestyle, discussing issues such as physical activity, nutrition, preventive behavior, stress control and social relationship as well as assessing some anthropometric indicators of obesity, cardiovascular and metabolic risk. This is a descriptive comparative correlational study, where 53 civil servants were evaluated, being 19 male and 34 female. It was applied the instrument “pentacle of wellness”, the questionnaire of habitual physical activity also the IMC, RCQ, CC and RCE were measured. It was verified that the components physical activity, nutrition and stress control require further attention, 64% of the participants are inactive, there is no significant difference between men and women regarding to the components of the Pentacle of Wellness or to the habitual physical activities (p = 048). The RCE pointed a correlation with the components nutrition (Cho = 0.30), physical activity (Cho = 0.51), and stress control (Cho = - 0.40). It was also verified a correlation between the age and IMC (r = 0.55), CC (0.53) and RCE (r = 0.60). Thus, it was identified a high percentage of inactive employees and with values ??of anthropometric indicators of obesity, cardiovascular and metabolic risk over the reference values ??and lived experience points to a need for developing other health-related interventions within the ambit of the IFPE.
Keywords: Education; Health; School